ANOHOVY FISHERY OF SOUTHWEST COAST OF INDIA WITH NOTES ON CHARACTERISTICS OF THE RESOURCES - Luther, G (Indian Journal of Fisheries, 2011)
A study of the monthly anchovy fishery data from the eleven fishery surveyzones along the southwest coast of India lying between Cape Comorin and thenorthern border of Kerala coast has revealed that the southern region lying betweenCape Comorin and Quilon is most productive for the anchovies, landing annuallya little over 10,000 tonnes. This forms about 70% of the anchovy catch landedalong the southwest coast. Stolephorus devisi ond S. bataviensis are the commerciallyimportant anchovies along the southern region. There are two fishery seasonsin the southern region, one during January-May and other during September-November; but only a single season extending from July to November is presentin the northern region. The main fishery season throughout the southwest coast,however, is during September-November. The possibility of increasing the anchovycatch between Quilon and Ratnagiri has been pointed out. The present state ofutilization of the catch and marketing are outlined, together with some suggestionsfor their improvement. Some details of thÂ« fisheries and biological characteristicsof the anchovies of the Vizhinjam area are given. As the anchovy fishery is mainlysupported by fishes of the 'O' year class, anchoviss are to be regarded as anaTinually renewable fishery resource. There is multiple spawning of individualfish and the spawning season of each species is also prolonged. The 'Nonnavu'fishery which takes a great toll of the young juvenile of Stolephorus spp., and itsimpact on the larger-sized anchovy fishery resources deserve detailed investigation